1995
DOI: 10.4037/ajcc1995.4.5.370
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of adolescent and young adult trauma victims

Abstract: BACKGROUND: Repeated injury, or recidivism, because of intentional or unintentional injury is a growing chronic health problem among urban adolescents and young adults in the United States. OBJECTIVE: To describe demographic, social, environmental, psychological, and developmental antecedents and risk-taking behaviors, and to examine their relationships to type of trauma and rate of trauma recidivism in adolescent and young adults in an urban trauma center. METHODS: One hundred adolescent and young adult traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Neglect and higher rates of driving under the influence may in part explain the increased risk of trauma in AODD family members. Moreover, aggression is common among children of people with AODD [28] and is in turn predictive of risk‐taking behaviors in adolescents [29]. Although there are no studies comparing these effects in the family members of alcoholics with those of diabetics or asthmatics, the nature of AODD makes it plausible that these particular stressors are more pronounced among family members of people with AODD.…”
Section: Discussionmentioning
confidence: 99%
“…Neglect and higher rates of driving under the influence may in part explain the increased risk of trauma in AODD family members. Moreover, aggression is common among children of people with AODD [28] and is in turn predictive of risk‐taking behaviors in adolescents [29]. Although there are no studies comparing these effects in the family members of alcoholics with those of diabetics or asthmatics, the nature of AODD makes it plausible that these particular stressors are more pronounced among family members of people with AODD.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to be concerned about alcohol consumption among adolescents, but the negative consequences, i.e. problem behaviour occurring in connection with alcohol consumption such as antisocial problematic behaviour, interpersonal violence, weaponcarrying and fighting, sexual risk-taking such as early debut and a large number of partners Hillbom et al, 1995;Murdoch et al, 1990;Redeker et al, 1995;Shrier et al, 1997), are perhaps the most urgent issues. Antonovsky (1993) argues that individuals with a strong SOC have a set of fundamental rules and flexible tactics to cope with or successfully process information, which makes conflict resolution possible.…”
Section: Discussionmentioning
confidence: 99%
“…Bagnall (1988), on the other hand, suggested that patterns of early alcohol use bear little relation to alcohol behaviour in adults. Problem behaviour, such as interpersonal violence, weapon-carrying and fighting, sexual risk-taking such as early debut and a large number of partners, and medical conditions such as cerebral infarction have been reported to be related to alcohol consumption among adolescents and young adults (DuRant, Kahn, Beckford & Woods, 1997;Hillbom, Haapaniemi, Juvela, Palomaki, Numminen & Kaste, 1995;Redeker, Smeltzer, Kirkpatrick & Parchment, 1995;Shrier, Emans, Woods & DuRant, 1997). There is a strong statistical association between alcohol use, antisocial problematic behaviour and violent crime (Murdoch, Pihl & Ross, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This study illustrates a tight association between the unemployment rate and the rate of penetrating trauma occurring within a community. Although previous studies [1][2][3][4][5] have shown a high rate of unemployment among patients who are admitted for trauma, few have evaluated the direct effect that evolving social conditions have on local medical centers and law enforcement agencies. Interestingly, a previous study, 10 published since the submission and acceptance of the abstract of this article, documented a similar strong association between penetrating trauma and the unemployment rate at 2 level I trauma centers in a Midwest city.…”
Section: Commentmentioning
confidence: 99%
“…One reason for this fluctuation may be changes in the socioeconomic conditions of our community. Previous studies [1][2][3][4][5] have demonstrated that the rate of unemployment among trauma victims is higher than that among the general population. However, these studies include a limited number of patients evaluated during a short period.…”
mentioning
confidence: 99%